2014
DOI: 10.15381/rivep.v25i2.8494
|View full text |Cite
|
Sign up to set email alerts
|

EFECTO DE DIETAS ENRIQUECIDAS CON VITAMINA E Y SELENIO ORGÁNICO EN EL COMPORTAMIENTO PRODUCTIVO Y CALIDAD FUNCIONAL DEL FILETE DE TRUCHA ARCO IRIS (Oncorhynchus mykiss).

Abstract: RESUMENEl objetivo del presente estudio fue evaluar dietas enriquecidas con vitamina E y selenio orgánico sobre el comportamiento productivo y la calidad funcional del filete de truchas arco iris (Oncorhynchus mykiss). El estudio se hizo en el Centro Piscícola «El Ingenio» en Huancayo, Perú, con 4200 truchas juveniles (164 g de peso) durante 40 días. Se trabajó con una dieta basal (tratamiento 1), dos niveles de vitamina E (25 y 50 ppm y tres niveles de selenio orgánico (0.15, 0.25 y 0.35 ppm). Se asignaron 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…In our study, an increase of current feed selenium level (0.25 mg selenium•kg −1 ) to maximum approved levels in the European market (0.5 mg selenium•kg −1 ) with a selenised-yeast led to a 2.9-fold increase for selenium contents in trout fillets. Although variable in the magnitude of selenium deposition, previous studies have also reported the successful Se fortification of fish fillets (Hunt et al, 2011;Küçükbay et al, 2009;Pacitti et al, 2015;Rodríguez & Rojas, 2014). The utilization of organic Se sources, as selenised-yeast, is also advantageous, since organic bound selenium was found to be a higher bioavailable form of Se when compared to inorganic sources in rainbow trout fortification studies (Küçükbay et al, 2009;Rider et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increase of current feed selenium level (0.25 mg selenium•kg −1 ) to maximum approved levels in the European market (0.5 mg selenium•kg −1 ) with a selenised-yeast led to a 2.9-fold increase for selenium contents in trout fillets. Although variable in the magnitude of selenium deposition, previous studies have also reported the successful Se fortification of fish fillets (Hunt et al, 2011;Küçükbay et al, 2009;Pacitti et al, 2015;Rodríguez & Rojas, 2014). The utilization of organic Se sources, as selenised-yeast, is also advantageous, since organic bound selenium was found to be a higher bioavailable form of Se when compared to inorganic sources in rainbow trout fortification studies (Küçükbay et al, 2009;Rider et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, positive or negative changes in the fish health appear to be closely associated to the internal selenium amounts. When selenium concentrations in the body exceed the optimum level and start to accumulate in higher quantity in various fish tissues such as the muscle, liver, and kidney tissues, then exerts negative impact on the health of fish and cause toxicities (Hilton et al 1980;Raza 2012;Jamil 2013;Rodríguez and Rojas 2014).…”
Section: Selenium Deficiency and Its Surplus Amountsmentioning
confidence: 99%
“…The combined supplementation of vitamin E (50 ppm) and selenium (0.35 ppm) showed positive interaction with each other and significantly enhanced the gain weight and feed conversion ratio in rainbow trout (Oncorhynchus mykiss). Additionally, the flesh quality was also improved than in the control group (Rodríguez and Rojas 2014). Goes et al (2016) worked on the supplementation of selenium and vitamin E in diets for pacu (Piaractus mesopotamicus) and described that the supplementation of 1 mg Se kg −1 in combination with 200 mg vit E kg −1 considerably decreased the oxidation process in the meat which led to improved maintenance performance and body incomes.…”
Section: Selenium Interaction With Other Trace Elements and Vitamins mentioning
confidence: 99%
“…There was also an improvement of the fillet´s functional quality when compared to control (Rodríguez and Rojas, 2014).…”
Section: Resultsmentioning
confidence: 80%